Analysis of Business Income of Various Small and Medium Enterprises of Cassava-Based Snacks - Yuliana, Yuliana; Oktarina, Yetty; Efrianti, Rini; Kurnia, Dadang (Agribusiness Journal, 2024)
This study aims to determine the amount of income of various cassava-based snack food SMEs in Martapura District, East Ogan Komering Ulu Regency. The method used in this research is the quantitative descriptive analysis method. Sampling techniques using the saturated sample method. The data analysis technique used is income analysis. Based on the results of research and analysis that has been done, it is concluded that the income of Kelanting SMEs in Martapura District, East Ogan Komering Ulu Regency is Rp. 7.479. 067/month. The income of yam chips SMEs in Martapura District, East Ogan Komering Ulu Regency is Rp. 10,521,428 /month, and the income of yam chips and kelanting SMEs in Martapura District, East Ogan Komering Ulu Regency is Rp. 11.397.575/month.